2016
DOI: 10.21512/tw.v17i1.1810
|View full text |Cite
|
Sign up to set email alerts
|

Factors of Consumer Behavior That Affect Purchasing Decisions on Blackberry Smartphone

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…In their research, Al-Ghaswyneh; Lawan et al; and Nawawi et al [1,35,36] indicated that cultural factors have a significant effect on one's buying decision. The study of Etuk et al [37] indicates that that family, reference groups, and culture have a significant positive influence on the decision-making process regarding purchases.…”
Section: Consumermentioning
confidence: 97%
“…In their research, Al-Ghaswyneh; Lawan et al; and Nawawi et al [1,35,36] indicated that cultural factors have a significant effect on one's buying decision. The study of Etuk et al [37] indicates that that family, reference groups, and culture have a significant positive influence on the decision-making process regarding purchases.…”
Section: Consumermentioning
confidence: 97%
“…Regarding the relationships amongst self-consciousness, information seeking, decision making and post-purchase satisfaction, research has shown that self-consciousness affects information seeking, which in turn affects decision making and post-purchase satisfaction (Lee & Hwang, 2019). Meanwhile, other consumers' behavioural factors such as cultural, social, personal and psychological factors also influence their purchasing decisions (Fishbein & Ajzen, 2005;Nawawi, 2016).…”
Section: Theoretical Framewokmentioning
confidence: 99%
“…Menurut Nawawi (2016) purchase decision adalah keputusan konsumen dalam melakukan pembelian suatu produk yang dipengaruhi oleh berbagai faktor bisa dari dalam diri sendiri ataupun dari luar diri seperti lingkungan.…”
Section: Purchase Decisionunclassified